2018
DOI: 10.1111/tbed.13004
|View full text |Cite
|
Sign up to set email alerts
|

First detection and genetic analysis of fox‐origin porcine circovirus type 2

Abstract: Porcine circovirus type 2 (PCV2) is a causative agent of porcine circovirus-associated disease (PCVAD), which is a serious problem in the swine industry worldwide. In recent years, nonporcine-origin PCV2 has attracted more and more attention of the researchers. This study reported on the first identification of PCV2 in farmed foxes with reproductive failure. Three fox-origin PCV2 strains were successfully isolated, sequenced and designated as FoxHB1, FoxHB2 and FoxHB3, respectively. Pairwise-sequence compariso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 31 publications
4
32
1
Order By: Relevance
“…When we compared the BLV infection rate among the 6 test areas, we observed that the highest infection rate was in Yangon region (58.70%) and the lowest was in Kayin State (24.44%). The BLV infection rate among the cattle of Myanmar reported in this study was higher than that reported in some Asian countries: Philippines (4.8-9.7%) [28] and India (27.9%) [36]. However, the BLV infection rate in this study was close to or lower than that in Korea (42.16%) [29], Thailand (58.74%) [32], and China (49.11%) [46].…”
Section: Discussioncontrasting
confidence: 72%
See 3 more Smart Citations
“…When we compared the BLV infection rate among the 6 test areas, we observed that the highest infection rate was in Yangon region (58.70%) and the lowest was in Kayin State (24.44%). The BLV infection rate among the cattle of Myanmar reported in this study was higher than that reported in some Asian countries: Philippines (4.8-9.7%) [28] and India (27.9%) [36]. However, the BLV infection rate in this study was close to or lower than that in Korea (42.16%) [29], Thailand (58.74%) [32], and China (49.11%) [46].…”
Section: Discussioncontrasting
confidence: 72%
“…The results of this study are more accurate than that from our earlier study on BLV strains isolated from Nay Pyi Taw Union Territory, which detected only genotype-10 in Myanmar [33]. This study also demonstrated that the three BLV genotypes, genotype-1, genotype-6 and genotype-10, were similar to those identified in the neighboring countries of Myanmar [32,36,45,46]. Interestingly, the BLV strains belonging to genotype-6 clustered into 3 subgenotypes and the BLV strains belong to the subtype-6a had distinct nucleotide and amino acid substitutions.…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…In recent years, cases of infections due to porcine pathogens (such as Hepatitis E virus, Pseudorabies virus) have progressively in minks and foxes (41)(42)(43)(44). PCV2 was also reported in minks, foxes, and raccoon dogs with diarrhea or reproductive failure in China (45)(46)(47). Interestingly, the samples were tested negative for common pathogens (such as Mink enteritis virus, Canine distemper virus, Coronavirus, Rotavirus, or Astrovirus) of minks and foxes, indicating that PCV2 was also an important pathogen contributing to the clinical diseases of minks and foxes.…”
Section: Pcvs In Caninesmentioning
confidence: 99%